Role of Neuroinflammation in Amyotrophic Lateral Sclerosis: Cellular Mechanisms and Therapeutic Implications - Liu, Jia; Wang, Fei (Frontiers in Immunology, 2017)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that affects upper motor neurons comprising the corticospinal tract and lower motor neurons arising from the brain stem nuclei and ventral roots of the spinal cord, leading to fatal paralysis. Currently, there are no effective therapies for ALS. Increasing evidence indicates that neuroinflammation plays an important role in ALS pathogenesis. The neuroinflammation in ALS is characterized by infiltration of lymphocytes and macrophages, activation of microglia and reactive astrocytes, as well as the involvement of complement. In this review, we focus on the key cellular players of neuroinflammation during the pathogenesis of ALS by discussing not only their detrimental roles but also their immunomodulatory actions. We will summarize the pharmacological therapies for ALS that target neuroinflammation, as well as recent advances in the field of stem cell therapy aimed at modulating the inflammatory environment to preserve the remaining motor neurons in ALS patients and animal models of the disease.